2005
DOI: 10.1007/s10334-005-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution MR imaging appearance of colonic tissue in rabbits using an endoluminal coil

Abstract: Dedicated endoluminal RF coil provides good spatial resolution at the region of interest. On this prospective study of in vivo rabbit, evaluation of colon walls allowed to provide detailed information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…At clinical field strength, imaging of small regions of interest obtained from endoluminal coils exhibits a higher signal‐to‐noise ratio than with external coils (5). Applications such as high‐resolution imaging of the colon or esophagus walls could be highly useful for clinicians (6). On another part, in several diagnosis or therapeutic procedures, patients could have metallic implants (pacemaker), electrodes (eg deep EEG, stimulation electrodes), or catheter, with in some cases a part of it in the patient's body and the other part outside the patient.…”
Section: Introductionmentioning
confidence: 99%
“…At clinical field strength, imaging of small regions of interest obtained from endoluminal coils exhibits a higher signal‐to‐noise ratio than with external coils (5). Applications such as high‐resolution imaging of the colon or esophagus walls could be highly useful for clinicians (6). On another part, in several diagnosis or therapeutic procedures, patients could have metallic implants (pacemaker), electrodes (eg deep EEG, stimulation electrodes), or catheter, with in some cases a part of it in the patient's body and the other part outside the patient.…”
Section: Introductionmentioning
confidence: 99%
“…A rectangular single loop coil was designed using a 35 µm-thick copper trace (width w = 5.1 mm, and length l = 47 mm on a FR4 substrate (relative permittivity r = 4, thickness t = 0.8 mm). Previous in vivo works (Armenean et al 2004, Pilleul et al 2005 have demonstrated that such size and geometry of the loop enable the depiction of bowel abnormalities by imaging the colon wall layers with an adequate penetration depth and a high in-plane spatial resolution. Figure 1 shows the photograph and the electric circuit of the different used coils.…”
Section: Coils Prototypesmentioning
confidence: 99%
“…Indeed, despite the huge progresses in radiofrequency (RF) coils, based on the phased array technology with increase of channels (Giusti et al 2012), the external MRI coils have remained unable to provide adequate SNR to reach required high spatial resolution images. By comparison several authors have demonstrated that internal coils significantly increase the local SNR and makes possible either to perform fast in vivo MR spectroscopy of heart tissues or to obtain high spatial resolution MR images of colon walls in preclinical context , Dorez et al 2016, Kantor et al 1984, Pilleul et al 2005, Ramgolam et al 2011.…”
Section: Introductionmentioning
confidence: 99%